2003
DOI: 10.1016/s0042-6989(03)00411-5
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of L- and M-cone driven ERGs in cone and cone–rod dystrophies

Abstract: To study the L- and M-cone pathways and their interactions in patients with cone and cone-rod dystrophies, ERG responses were measured to stimuli which modulated exclusively the L- or the M-cones, or the two simultaneously. The L- and M-cone driven ERG amplitudes were considerably reduced in the patients. The mean phases of the L-cone driven ERGs in the patients lagged those of normals significantly, whereas the mean M-cone driven ERGs were significantly phase advanced resulting in a substantial phase differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…These differences are enough to be detected by mean of the statistically significant increment observed in the slope of the fits. This increasing disability of cones with eccentricity is well known in typical RP and has been recently described as a result of a neural reorder occurring in the postreceptoral pathways after the local retinal dysfunction [18][19][20][21]. It is interesting to remark that, as happened with rod response in Figure 2, in Figure 3 slopes of linear fits for TRP3 and CRD patients are very similar to those measured for the control group.…”
Section: Discussionsupporting
confidence: 70%
“…These differences are enough to be detected by mean of the statistically significant increment observed in the slope of the fits. This increasing disability of cones with eccentricity is well known in typical RP and has been recently described as a result of a neural reorder occurring in the postreceptoral pathways after the local retinal dysfunction [18][19][20][21]. It is interesting to remark that, as happened with rod response in Figure 2, in Figure 3 slopes of linear fits for TRP3 and CRD patients are very similar to those measured for the control group.…”
Section: Discussionsupporting
confidence: 70%
“…The ERG signals are 150 ms extracts of 4 s traces that are the averages of 12 runs. Drift components in the electroretinographic responses to the L-and M-cone-isolating stimuli were suppressed by the removal of low frequency components [36] Fig. 5 Threshold contrasts in a "normal" trichromatic subject, a "normal" deuteranope (replotted from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[5,10,22,30,36] Genetic studies have revealed numerous genetic subtypes with different modes of genetic transmission (for a review see: http://www.sph.uth.tmc.edu/Retnet/).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations